ChemInform Abstract: Organocatalytic C—H Bond Arylation of Aldehydes to Bis‐heteroaryl Ketones. Issue 34 (1st August 2013) - Toh, Qiao Yan; McNally, Andrew; Vera, Silvia; Erdmann, Nico; Gaunt, Matthew J.
Abstract A wide range of heteroaromatic and an aliphatic aldehyde are applied in the reaction with symmetrical iodonium salts [(II), (VI)] to afford the ketones in excellent yields.